Recovery of proliferative cells up to 15- and 49-day postmortem from bovine skin stored at 25°C and 4°C, respectively. Issue 1 (1st January 2017) - Walcott, Brian; Singh, Mahipal
Abstract: The objective of this study was to assess the time limits within which proliferative cells can be recovered in bovine skin stored separately at 4 and 25°C after animal death. In the first experiment, skin explants ( n  = 110; 2–3 mm 2 ) from 11 animals stored at 4°C were cultured weekly up to 7 weeks in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 50 units/mL of penicillin, 50 μg/mL of streptomycin, and 2.5 μg/mL of fungizone. The presence/absence of fibroblast-like cell outgrowth around explants was scored. Out of 640 explants cultured, 567 (87%) adhered to dish surface, of which 333 (58.73%) exhibited outgrowth including 16.67% explants from 49 days postmortem tissues. Similarly, in the second experiment, when the tissues were stored at 25 ± 2°C prior to culturing on alternate days up to 17 days, 204 (48%) explants exhibited outgrowth that included 19.15% from 15 dpm tissues. The number of explants exhibiting outgrowth was inversely proportional to postmortem time interval in both temperatures studied. Secondary cultures established from outgrowth for selected time points showed stable chromosomes, normal GFP gene expression, and comparable growth morphology to fresh tissue-derived cells. The cells lasted in culture for more than 20 passages. These results suggest that live and usable cells can be recovered from bovine skin tissues up to about 2 weeks postmortem, if skin is stored at 25°C, and about three times more (>6 weeks), if stored at 4°C.